The Bolognese Societates Armatae of the Late 13th Century - Jürg Gassmann (Bern Open Publishing, 2015)
The Bologna archives preserve the bye-laws of 24 "armed societies", dating from between 1230 and the early 1300s, written in good notary Latin. Though known to exist in other Italian city-states, only few non-Bolognese armed society bye-laws are preserved. These armed societies had disappeared everywhere by the Late Middle Ages. This article explores the function of these armed societies and the feudal law aspects of the bye-laws - was their function predominantly military, social or political? Why did they suddenly appear, and just as suddenly disappear? How did they fit into Bologna's constitution - how did they relate to the civic authorities, the guilds? How did these armed societies operate? Who were the members? What arms did they have? Did they participate in the warfare between the city-states, the battles of the Lombard League and the Holy Roman Empire, the struggles between the Emperor and the Pope, the feuds between the Ghibellines and the Guelphs?